2011
DOI: 10.1063/1.3585021
|View full text |Cite
|
Sign up to set email alerts
|

Note: Development of a high resolution six-degrees-of-freedom optical vibrometer for precision stage

Abstract: A high resolution six degrees of freedom (6-DOF) optical vibrometer is proposed. 6-DOF vibrations can be simultaneously measured using the proposed optical vibrometer, which reduces measurement time and number. The performance of the proposed vibrometer is verified by experiments. The results show that the accuracy of the proposed optical vibrometer is ±30 nm∕200 nm and ±0.04 arcsec∕0.1 arcsec at 1000 Hz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, with the feedback of calibration results, it was confirmed that the tolerance error of the "100% coincidence" measured by the commercial laser interferometer was about ±5 arcsec, which could result in poor measuring repeatability, especially for the case of long-range measurements, as shown in Figure 2a. Therefore, an altitude angle adjustment module composed of a beam splitter, a convex lens, and a QD was proposed based on the autocollimator principle [18] for obtaining higher calibration repeatability, as shown in Figure 2b and Figure 3. With the proposed module, the reflected beam was deflected by the beam splitter and passed through a convex lens onto QD, and the tolerance error of the "100% coincidence" could be reduced to ±1 arcsec.…”
Section: Pentaprism Modulementioning
confidence: 99%
“…However, with the feedback of calibration results, it was confirmed that the tolerance error of the "100% coincidence" measured by the commercial laser interferometer was about ±5 arcsec, which could result in poor measuring repeatability, especially for the case of long-range measurements, as shown in Figure 2a. Therefore, an altitude angle adjustment module composed of a beam splitter, a convex lens, and a QD was proposed based on the autocollimator principle [18] for obtaining higher calibration repeatability, as shown in Figure 2b and Figure 3. With the proposed module, the reflected beam was deflected by the beam splitter and passed through a convex lens onto QD, and the tolerance error of the "100% coincidence" could be reduced to ±1 arcsec.…”
Section: Pentaprism Modulementioning
confidence: 99%
“…They use a BS (beam splitter) to evenly distribute the light emitted by a single laser light source to two angle measuring probes. The measurement accuracy of roll, pitch and yaw angles is 0.04″ [11]. However, they only reduced the number of light sources, the two measuring probes are still arranged in the orthogonal direction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such a goniometer occupies a large space and has a complex structure, thereby making its installation and adjustment difficult. Hsieh et al constructed an orthogonal dual autocollimation right-angle measurement system using a beam splitter and a single laser light source to measure roll, pitch, and yaw angles with an accuracy of up to 0.04 ′′ [10]. However, despite reducing the number of light sources, the probe still occupied a large space, and its working distance was short.…”
Section: Introductionmentioning
confidence: 99%